Can green attitude complement the influence of green marketing on green purchase intention for fast food products? - Hermanto Hermanto; Astuti Widji; Sugito Pudjo; Triatmanto Boge (Journal of Economics and Management)
– This study aims to determine whether a green attitude can complement the influence of green marketing on green purchase intention for environmentally friendly fast-food products, considering the orientation toward sustainable environmental preservation.